2017
DOI: 10.18632/oncotarget.20674
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparative study of progression-free survival and overall survival between metachronous and synchronous metastatic renal cell carcinoma in intermediate- or poor-risk patients treated with VEGF-targeted therapy

Abstract: IntroductionThe aim of this study was to compare progression-free survival (PFS) and overall survival (OS) between metachronous and synchronous metastatic renal cell carcinomas treated with VEGF-targeted therapy.MethodsBetween 2005 and 2014, 93 (78.8%) intermediate- and 25 (21.2%) poor-Heng-risk patients, including 32 (27.1%) patients with metachronous and 86 (72.9%) patients with synchronous renal cell carcinoma, were enrolled retrospectively. PFS and OS values were compared according to the number of risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
9
0
3
Order By: Relevance
“…Generally, metachronous metastasis (MM) is considered to have a better prognosis than synchronous metastasis (SM) in the field of metastatic RCC . It can be explained by the presence or absence of primary tumors following nephrectomy, or the distinct phenotypes with different ontogenetic activities between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, metachronous metastasis (MM) is considered to have a better prognosis than synchronous metastasis (SM) in the field of metastatic RCC . It can be explained by the presence or absence of primary tumors following nephrectomy, or the distinct phenotypes with different ontogenetic activities between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, metachronous metastasis (MM) is considered to have a better prognosis than synchronous metastasis (SM) in the field of metastatic RCC. 23,24 It can be explained by the presence or absence of primary tumors following nephrectomy, or the distinct phenotypes with different ontogenetic activities between the two groups. Kim et al 24 reported that MM is associated with more favorable survival outcomes than SM in patients with metastatic RCC treated with VEGF-TKIs (OS, 20.1 vs 9.6 months, P = 0.010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Tanaka et al [8] of 245 patients with mRCC, approximately one-quarter of the patients were reclassified into different risk groups of the IMDC model after TT administration in the first-line and second-line settings; the [19]. TFI with a 1-year cut-off came from the time from diagnosis to treatment from the Heng risk criteria [5], which is a well-known prognostic risk factor for mRCC [20][21][22][23]. It indirectly depicted the growth rate and aggressiveness of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…First, the prognosis of metachronous tumors are better than that of synchronous tumors. 15 Second, Zheng et al 26 showed different mutational patterns between synchronous and metachronous liver metastases of colorectal cancer. Third, a systematic review of colorectal cancer studies identified significant differences in expression of molecular markers between synchronous and metachronous metastases.…”
mentioning
confidence: 99%